Mycosis Fungoides Exhibits the Features of Skin Tags: A Case Report - Zhang X; Wang P (Dove Medical Press, 2023)
XiaoYan Zhang, Ping Wang Department of Dermatology, Hangzhou Third People's Hospital, Hangzhou, People's Republic of ChinaCorrespondence: Ping Wang, Department of Dermatology, Hangzhou Third People's Hospital, Hangzhou, People's Republic of China, Tel +86-13588812862, Email dermwang@aliyun.comAbstract: We present the case of a 37-year-old male diagnosed with Mycosis fungoides (MF) after gradually developing multiple skin tags and brownish lichenoid papules. The patient had pre-existing erythema over his entire body, especially his face, upper extremities, and trunk, for over 1.5 years. Microscopic examination of the papule and the skin tag (ST) exhibited similar features mainly characterized by superficial dense band-like lymphoid infiltrates and epidermotropism of atypical lymphocytes (Pautrier's micro-abscesses). Immunohistochemistry further revealed the lymphoid infiltrates predominantly expressed LCA, CD3, CD4, and CD45RO but lacked CD7, CD8, CD30, CD20, and CD79a. The finding of this study that reports MF characterized by unusual STs suggests that some causes and effects have not been previously described in MF.Keywords: skin tags, lymphoma, T-Cell, cutaneous, mycosis fungoides